ENHANCING LEGAL LITERACY: UNDERSTANDING THE SIGNIFICANCE OF LAW NO. 9/2019 ON ELECTRONIC TRANSACTIONS IN THE SOCIAL MEDIA ERA - Gunawan Widjaja (JOURNAL OF COMMUNITY DEDICATION, 2022)
In the backdrop of the social media era's transformative impact on society, this research embarked on a quest to unravel the pivotal role of Law No. 9/2019 on Electronic Transactions. This retrospective study delved into the legal complexities and ethical considerations inherent in the digital age. Employing a meticulous research design, the investigation encompassed a thorough literature review, a detailed legal analysis, and compelling case studies. Data collection involved an exhaustive review of legal documents, insightful interviews with legal experts, and a comprehensive analysis of pertinent court cases. The aim was to comprehensively dissect the legal landscape surrounding electronic transactions and social media. The study hinged on qualitative and quantitative data analysis, allowing for a multifaceted exploration of the subject matter. Ethical guidelines were rigorously followed throughout this scholarly endeavor, with an unwavering commitment to safeguarding privacy and data. The research aspired to provide valuable insights into the profound implications of Law No. 9/2019 on Electronic Transactions, not only in terms of its legal provisions but also its practical applications in the digital age. Ultimately, this retrospective analysis underscores the critical importance of legal literacy in navigating the intricate terrain of electronic transactions and social media. It highlights the enduring significance of the legal framework, such as Law No. 9/2019, in upholding the rights and responsibilities of individuals and businesses alike in the ever-evolving social media landscape.